Effects of Reflective and Micro-Teaching Practices on Teaching Skills and Attitude to Teaching Practice Among Pre-Service Teachers of English in Nigeria (2014)
A large number of pre-service English as Second Language (ESL) teachers trained in Nigeria have deficiencies in developing and demonstrating appropriate teaching skills and attitude during Teaching Practice (TP). This is probably as a result of their inadequate exposure to participatory practices like Reflective Teaching Practice (RTP) and Micro-Teaching Practice (MTP) during the exercise. Previous studies on RTP and MTP have focused on different areas of teacher behaviour but have not sufficiently covered the area of using them to improve the teaching skills and attitude of pre-service teachers. This study, therefore, determined the effects of RTP and MTP on teaching skills and attitude to teaching practice among pre-service teachers of English as second language in South-West and North-Central states of Nigeria. The moderating effects of the pre-service teachers‘ academic ability and gender on the dependent variables were also determined. Pretest-posttest, control group, quasi experimental research design was adopted. The participants were 120 pre-service ESL teachers selected through multistage sampling technique from six colleges of education in South-West (4) and North-Central (2) states. Participants were randomly assigned to RTP (40), MTP (40) and Control (40) groups respectively. Pre-service ESL Teachers‘ Attitude to Teaching Practice Questionnaire (r= 0.88), Classroom Observation Scale Manual (r= 0.79), Academic Ability Rating Sheet and two Instructional Guides, Micro Teaching Instructional Guide and Reflective Teaching Instructional Guide (r = 0.81 and r = 0.88) were the instruments used. Seven hypotheses were tested at 0.05 level of significance. The treatment lasted 12 weeks. Data were analysed using Analysis of Covariance, and Scheffe‘s post-hoc test. There was a significant main effect of treatment on ESL pre-service teachers‘ teaching skills (F(2, 103) = 22.78; η2 = .31). Pre-service ESL teachers exposed to MTP had highest teaching skill mean score (= 96.37), those exposed to RTP had (= 91.82) and control (= 76.84). There was also a significant main effect of treatment on the attitude of pre-service ESL teachers to teaching practice (F (2, 103) = 5.82; η2 = .10). Pre-service ESL teachers exposed to RTP had highest post attitude mean score (= 61.78), than those exposed to MTP (=59.75) and those exposed to conventional teaching practice (= 52.83). There were no significant main effects of academic ability and gender on pre-service ESL teachers‘ teaching skills and attitude towards teaching practice. Also, there were no significant interaction effects of treatments and each of teachers‘ academic ability and gender. Micro-teaching practice and reflective teaching practices enhanced the pre-service ESL teachers‘ teaching skills and attitude towards teaching practice, though the latter was more effective in Nigeria. These strategies should be adopted in improving the teaching skills of pre-service teachers of English as second language.